2021
DOI: 10.26907/esd.16.2.05
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service teachers’ concerns about social robots in the classroom: A model for development

Abstract: Social robots are being tested in the educational arena with current thinking in two main directions. One is arguing for the benefits of robots in affective and efficient instruction and is more teachercentered. Within the second, more student-centered oriented, proponents of human uniqueness are raising long-term concerns. Teacher-centeredness and student-centeredness form pedagogical beliefs underpinning teachers’ attitudes guiding technology integration. Limited research has explored teachers’ underlying be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 54 publications
(176 reference statements)
2
23
0
Order By: Relevance
“…[52,53]. Istenic et al (2021) identified participants' negative attitudes and a clear rejection of humanoid robot technology and social skills in the classroom [54]. Participants in the study do not reject social robots as such, but in their point of view, robots do not have the status of a social entity capable of engaging in student-centered teaching and caring for the child's well-being and development.…”
Section: Resultsmentioning
confidence: 96%
“…[52,53]. Istenic et al (2021) identified participants' negative attitudes and a clear rejection of humanoid robot technology and social skills in the classroom [54]. Participants in the study do not reject social robots as such, but in their point of view, robots do not have the status of a social entity capable of engaging in student-centered teaching and caring for the child's well-being and development.…”
Section: Resultsmentioning
confidence: 96%
“…Teachers do not have a clear idea of what social robots could be used for [17]. Hrastinski et al [18] and Istenič et al [19] add that it is not clear to education professionals why social robots should be used in the classroom and why they should have the appearance of a human being.…”
Section: Literature Review 21 the Use Of Social Robots In The Educati...mentioning
confidence: 99%
“…In the past decades, researchers and clinicians have raised concerns on the ethical and legal issues related to the robot-based intervention and the data collection associated with this (e.g., [34][35][36]. One of the ethical issues concerns privacy.…”
Section: Open Accessmentioning
confidence: 99%